True prevalence of long COVID in children: a narrative review - Esposito, Susanna; Deolmi, Michela; Ramundo, Greta; Puntoni, Matteo; Caminiti, Caterina; Principi, Nicola (Frontiers in Microbiology, 2023)
Contrary to what is true for adults, little is known about pediatric long COVID (LC). Studies enrolling children are relatively few and extremely heterogeneous. This does not allow to draw definitive conclusions on the frequency and pathogenesis of pediatric LC and limits the development of measures to contain the impact of this condition on the pediatric population. Depending on the methods used to collect and analyze data, studies have found that the incidence rate of pediatric LC may vary from about 25% to less than 5%.However, despite true prevalence of pediatric LC cannot be exactly defined, studies comparing children with previous COVID-19 and uninfected controls have shown that most of the clinical manifestations detected in infected children, mainly mood symptoms, mental health disorders and heart abnormalities could be diagnosed with similar frequency and severity in uninfected subjects also. This seems to indicate that SARS-CoV-2 is the cause of pediatric LC only in a part of children and other factors play a relevant role in this regard. Pandemic itself with the persistent disruption of child lives may have caused persistent stress in all the pediatric population causing mood symptoms, mental health disorders or several organ and body system functional alterations, regardless SARS-CoV-2 infection. These suppositions suggest the need for long-term physical control of all the children after COVID-19 especially when they were already suffering from an underlying disease or have had a severe disease. Moreover, attention should be paid to the assessment of change in children's emotional and behavioral functioning in order to assure adequate interventions for the best emotional and behavioral well being. However, whatever its origin, it seems highly likely that the prevalence of the pediatric LC is set to decline in the future. Preliminary observations seem to suggest that recently developed SARS-CoV-2 variants are associated with less severe COVID-19. This suggests that, as already seen in adults, a lower number of pediatric virus-associated LC cases should occur. The use of COVID-19 vaccines, reducing incidence and severity of SARS-CoV-2 infection, may reduce risk of LC development. Elimination of restrictive measures should reduce mood symptoms and mental health disorders.